Precise Positioning Control Strategy of Machine Tools: A Review - Anang, Nur Amira; Abdullah, Lokman; Jamaludin, Zamberi; Retas, Zain; Tsung Heng, Chiew; Syed Salim, Syed Najib (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this article, a precise positioning control strategy for the nonlinearity of machine tools is thoroughly reviewed. Precise positioning is crucial in machine tools industry where nonlinear phenomenon must be considered. Therefore, this paper aims to review various techniques used to enhance the precision of nonlinearity of machine tools. In the introduction, a significant review of machine tools is discussed based on deadzone phenomenon and high bandwidth. After that, linear control strategies are reviewed involving Proportional-Integral-Derivative (PID) and Cascade P/PI controller. This is followed by nonlinear control strategies, Nonlinear PID (NPID), Adaptive NPID (ANPID), Feedforward NPID (FNPID), Adaptive Robust Controller (ARC), Nominal Characteristics Trajectory Following (NCTF) controller and lastly, the fuzzy and neural network control is then reviewed. Finally, conclusions are presented according to the past researches conducted. Further studies regarding the topic can be improved by the implementation of several additional modules such as deadzone and feedforward compensators and disturbance observer that focus on both disturbance forces such as cutting force and friction force.